Activación de mastocitos en el intestino, una de las causas orgánicas en el síndrome de intestino irritable - Beltrán M., Caroll; Lobo A., Beatriz; Landskron R., Glauben; Defilippi G., Claudia; Madrid S., Ana María (Revista Hospital Clínico Universidad de Chile, 2012)
Irritable bowel syndrome (IBS) is one of the most common digestive health conditions in Chile as in the Western society, which is characterized by abdominal discomfort associated with alterations in bowel habit, that lead to increased visceral hypersensitivity. It has a significant impact on our country’s social welfare and economic development, due to great deterioration in the patient’s quality of life. Although the pathophysiology of IBS is unclear, the gut-brain axis disequilibrium is involved in the disease onset. Psychosocial factors, such as stress and depression, have been linked to altered immune responses as enhanced intestinal mast cell activation, in proximity to colonic nerves, correlate with abdominal pain in IBS. This review is a brief summary of the role of increased mast cell activity in IBS, focusing specifically on influences over epithelial and neural function at the intestinal mucosa. The most promisingpreliminary therapeutics approaches, directed to reduce mast cell activation, are also included in this review.